(untitled) (Bangladesh Journal of Microbiology, 2020)
The mass public health principally depends on types and qualities of a range of food items in any neighborhood. In this very study the microbiological analysis of the most sold bottled waters, fruit juices and dairy fluids consumed by the maximum children, carbonated soft drinks and the energy drinks especially consumed by young people was conducted with the simple isolation approach following the traditional microbiological methodology. Presence of Staphylococcus spp. was detected in 50% samples the results for the presence of enteric bacteria; fecal coliforms and Vibrio spp. were completely negative. On the basis of the quantification of total bacteria and of the staphylococcal species, more emphasis on the good manufacturing practice (GMP) as well as on the market complaints is suggested. Bangladesh J Microbiol, Volume 36 Number 2 December 2019, pp 115-117